(untitled) (Research, Society and Development, 2022)
The development of healthier and tasty chocolate cakes with substitution of traditional ingredients by functional ingredients is still a challenge for the food industry. The aim of this study was to evaluate the physicochemical and sensory characteristics of chocolate cakes made with two different concentrations of green banana flour (GBF) + wheat flour (WF) and hydrated chia + fat, sugar, cocoa powder and eggs by using the Plackett-Burman experimental design (PB12). It was observed that a decrease in WF, GBF and sugar resulted in an increase of water activity, volume and adhesion force. Moreover, an increase in WF, GBF, egg, chia, and sugar resulted in an increase on firmness, elasticity and crust colour. The scanning electron microscopy showed a porous and weak structure for formulations with GBF and chia seeds. The highest scores for the overall acceptability were found for formulations with 75% of GBF in replacement of WF and 50% of chia seeds as fat substitution agent associated with low levels of eggs, sugar and cocoa powder. These results indicate the potential use of chia seeds and GBF in combination to manufacture healthier chocolate cakes.